Mechanical Thrombectomy with Rotarex System in Buerger's Disease - Kilickesmez, Ozgur; Oguzkurt, Levent
We report the case of a patient with 2-month history of chronic thromboembolism of the distal superficial femoral and popliteal arteries with diagnostic features of thromboangiitis obliterans disease. The occlusion could not be crossed by antegrade approach and was achieved retrogradely via dorsalis pedis artery puncture followed by mechanical removal of the thrombus with Rotarex system (Straub Medical AG, Wangs, Switzerland). Subsequent ballooon angioplasties achieved exclusion of the thrombus, and straight-line flow established to the foot through the anterior tibial Artery. The present case report demonstrates the success of mechanical thrombectomy in a patient with Buerger's vasculitis.